"It Just Shifted Everything in Our Family Dynamic:" Recalibration within the Family System in Response to Alzheimer's Disease. Issue 2 (3rd April 2022) - Miller-Ott, Aimee E.; Cooper, R. Amanda; Lobdell, Evan
ABSTRACT: Alzheimer's disease (AD) is a debilitating progressive illness that wreaks havoc on the person with Alzheimer's (PWA) and their family. AD impairs the PWA's cognitive, communicative, and bodily functioning, and family members are challenged to maintain ongoing but significantly altered relationships with the PWA. We aimed to understand how the actions of family members of a PWA served to recalibrate the family system. Among the changes that recalibrated the family system was the renegotiation of roles in family subsystems that positioned family members as ingroup or outgroup members based on acceptable and legitimate support provision. Family members also began focusing on logistics of care and aimed to create "new normal" ways of interacting with the PWA that were painful but necessary for continued connection. This research has implications for what grief looks like with AD, how family members judge support, and how counselors can best work with family members.